Next-Generation Genetic Testing in the Diagnostics of Neurological Disease in Southwest Finland in 2010-2021: A Register-Based Study - Loukiainen, Saga; Haanpää, Maria K.; Martikainen, Mika H. (John Wiley & Sons, 2026)
Neurological disorders are heterogeneous and sometimes challenging to diagnose. Next-generation sequencing (NGS) panels and exome sequencing methods are increasingly advocated as first-tier genetic investigations. In this retrospective, single-centre, register-based study, we investigated the use of NGS-based investigations in the diagnostics of adult neurological disease at Turku University Hospital (TUH) (Turku, Finland) during 2010–2021. We identified patients who underwent any genetic testing to investigate neurologic disease in 2010–2021. NGS gene panel studies and exome investigations were scrutinised further. Data were collected from the TUH electronic medical records. We identified N = 844 patients (347 men and 497 women) who fulfilled the initial inclusion criteria. In this group, 331 NGS panels and 99 exome analyses were performed. The median age at the time of the first included genetic test was 45 years (range: 16–96 years). The diagnostic rate was 19% for all NGS-based studies. Amongst different patient groups, the diagnostic yield was highest in developmental and intellectual disorders (39%), second highest in neuromuscular disorders (38%) and lower in epilepsy and ataxia (13% and 10%, respectively). Amongst neurological disorders, the diagnostic yield of genetic testing differs between different patient phenotypes and based on the genetic testing selection. Further studies are needed to determine optimal strategies, with the highest yield and lowest cost, for genetic investigations in neurological disorders.